The Pomegranate - Ali Sarkhosh; Jeffrey G. Williamson (EDIS, 2019)
This 6-page document profiles the pomegranate and discusses its production in Florida. Written by Ali Sarkhosh and Jeff Williamson and published by the UF/IFAS Horticultural Sciences Department, January 2019. http://edis.ifas.ufl.edu/mg056